2010
DOI: 10.3390/toxins2040367
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Osmotic Stress Regulatory Pathway in Morphogenesis and Secondary Metabolism in Filamentous Fungi

Abstract: Environmental stimuli trigger an adaptative cellular response to optimize the probability of survival and proliferation. In eukaryotic organisms from mammals to fungi osmotic stress, mainly through the action of the high osmolarity glycerol (HOG) pathway, leads to a response necessary for adapting and surviving hyperosmotic environments. In this review we show that the osmoadaptative response is conserved but not identical in different fungi. The osmoadaptative response system is also intimately linked to morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(76 citation statements)
references
References 88 publications
3
62
0
7
Order By: Relevance
“…Pbs2 phosphorylates the Hog1 protein (a mitogen-activated protein kinase) in S. cerevisiae as well as in Aspergillus nidulans (Panadero et al, 2006;Duran et al, 2010). HOG1 is part of the HOG pathway that is induced upon osmotic stress.…”
Section: Evidence For Pleiotropymentioning
confidence: 99%
“…Pbs2 phosphorylates the Hog1 protein (a mitogen-activated protein kinase) in S. cerevisiae as well as in Aspergillus nidulans (Panadero et al, 2006;Duran et al, 2010). HOG1 is part of the HOG pathway that is induced upon osmotic stress.…”
Section: Evidence For Pleiotropymentioning
confidence: 99%
“…Growth is indicated in green and no growth in black. [44][45][46] In our study, mesophilic species showed a trend toward higher tolerance to osmotic stress due to excess of sodium chloride, but without species-specific differences (Table S1). A similar concordance was observed between virulent and attenuated species of Lichtheimia.…”
Section: Discussionmentioning
confidence: 61%
“…Nevertheless, no correlation between tolerance to stress and the observed virulence could be made, in contrast to virulence of evolutionary derived fungi like Candida. [44][45][46] Yet, pathogens of the derived fungi are often adapted to their hosts, whereas mucoralean fungi seem to be not, which could explain why there is not obvious difference in stress tolerance between potential pathogenic and non-pathogenic species.…”
Section: Discussionmentioning
confidence: 99%
“…Osmoadaptation involves both physiological and genetic manifestations of adaptation to a low-water environment (Galinski 1995). Osmoadaptation in fungi mainly through the action of the high osmolarity glycerol mitogen-activated protein kinase (MAPK) signalling pathway leads to a response necessary for adapting and surviving hyperosmotic environments (Duran et al, 2010). The osmoregulation MAPK pathway is well conserved in fungi.…”
Section: Discussionmentioning
confidence: 99%